2023
DOI: 10.3390/foods12061209
|View full text |Cite
|
Sign up to set email alerts
|

Breeding Bread-Making Wheat Varieties for Organic Farming Systems: The Need to Target Productivity, Robustness, Resource Use Efficiency and Grain Quality Traits

Abstract: Agronomic protocols (rotation, tillage, fertilization and crop protection) commonly used in organic and conventional crop production differ significantly and there is evidence that modern varieties developed for conventional high-input farming systems do not have the combination of traits required for optimum performance in organic farming systems. Specifically, there is evidence that prohibition on the use of water-soluble, mineral N, P and K fertilizers and synthetic pesticide inputs in organic farming resul… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
9
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

3
2

Authors

Journals

citations
Cited by 11 publications
(66 citation statements)
references
References 101 publications
0
9
0
Order By: Relevance
“…grain protein concentration) and nutritional (e.g. grain phenolic concentrations) quality (Rempelos et al 2023). The positive correlations between plant height and Se-concentrations identi ed in this study suggests that another important nutritional quality parameter may be improved in organic farming systems via the development and/or selection of longer straw varieties for the organic farming sector.…”
Section: Species/varietymentioning
confidence: 56%
See 1 more Smart Citation
“…grain protein concentration) and nutritional (e.g. grain phenolic concentrations) quality (Rempelos et al 2023). The positive correlations between plant height and Se-concentrations identi ed in this study suggests that another important nutritional quality parameter may be improved in organic farming systems via the development and/or selection of longer straw varieties for the organic farming sector.…”
Section: Species/varietymentioning
confidence: 56%
“…However, if there are strong associations breeding and/or selection of new varieties with higher grain Se concentrtaion and similar or higher grain yield or yield stability, is likely to be easier for the organic sector which often uses taller varieties to reduce competition from weeds and reduce disease levels. This hypothesis is based on results from both the NUE-CROPS and QLIF trials which showed that the use of FYM results in a lower risk of lodging in common wheat compared with mineral N or NPK fertiliser applied at the same total N-input level (Rempelos et al 2020(Rempelos et al , & 2023. The lower lodging risk is therefore thought to increase the feasibility of breeding and selecting longer-straw varieties for the organic farming sector, since this may also co-select for increased processing (e.g.…”
Section: Species/varietymentioning
confidence: 99%
“…• greenhouse gas emissions from food production [38] Although many of the desirable impacts of specific agronomic practices shown in Figure 1 are well documented (see Table 1), Rempelos et al [3] describe that there are few studies in which the relative effects of (and interactions between) different agronomic parameters (e.g., rotation, tillage, fertilization, and crop protection) used in organic and regenerative farming were investigated. In addition, there are very few studies in which the relative importance of (and interactions between) environmental, crop genetic, and agronomic factors was investigated [3,35,[39][40][41]. However, such data are thought to be essential for the development of strategies that can mitigate the negative impacts of global climate change [18,19,37,38].…”
Section: Modeling Studymentioning
confidence: 99%
“…Regenerative and organic production methods generate very different soil physical, chemical, and biological background conditions compared with intensive farming systems [39,40]. As a result, there is an urgent need to develop/select crop genotypes that are suitable for regenerative, low-input, and organic production systems [39,40].…”
Section: Modeling Studymentioning
confidence: 99%
See 1 more Smart Citation